Case Report: Implementation of a Multi-Component Behavioral Health Integration Program in Obstetrics for Perinatal Behavioral Health - Flynn, Heather; Deichen Hansen, Megan; Shabaka-Haynes, Amandla; Chapman, Shay; Roussos Ross, Kay (Frontiers in Psychiatry, 2021)
Despite growing research and policy attention, perinatal mood and anxiety disorders remain prevalent, burdensome for families, and largely un-treated in the US. Researchers have documented an array of barriers to accurate detection, linkage with effective treatment, and improved outcomes for perinatal women with behavioral health disorders. It is clear that a multi-component approach that integrates evidence-based detection and management of perinatal behavioral health in the context of obstetrics care can be effective. This paper presents the initial development of a program that includes evidence-based components of behavioral health integration in obstetrics in the state of Florida in the US. The FL BH Impact program, guided by the RE-AIM model for program implementation has been developed over the past two years. Program component implementation and preliminary findings are presented. Following the implementation phase, the program has enrolled 12 obstetrics practices and 122 obstetrics providers in program engagement and training activities. The primary program component allows for obstetrics clinician telephone access to comprehensive referral resources for patients and access to consultation with psychiatry. Since program implementation, the program has received a total of 122 calls to this line, with an expected increasing trajectory of calls over time. Results suggest that this program is feasible to implement in across a large geographic area. Challenges to implementation and future directions are discussed. These types of multi-component approaches to improved management and outcomes for PMAD are promising and must be expanded and sustained in the US.